Design processes for electronic books - Brunát, Tomáš (2012)
The thesis is engaged in the modeling of business processes, focusing on their design development, namely processes related to publishing electronic books. The main goal of the thesis is application of the EPC process modeling method for selected processes in a particular company Grada Publishing, a.s. The theoretical part is focused on process description, optimization, management and process modeling standards. The practical part is devoted to design development of the processes related to publishing e books under the EPC standards. Each process is described and if it was necessary to show more details of it, also other specifications were added. Once the process was developed, a theoretical optimization of its sales related sub process was designed proposed.